Peningkatan Produksi Kedelai Varietas Anjasmoro - Hasan Basri (Balitbangda Provinsi Lampung, 2018)
Efforts to increase soybean production are constrained by soil problems. The soil in Lampung area most of the Yellow Padsolik type of soil, characterized by the minimal availability of nutrients, but for the development of soybean is still wide open, especially now the government is seeking self-sufficiency in soybean in 2019. This study aims to see the influence bokashi on soybean production of varieties of anjasmoro. The research was conducted at Lampung Agricultural Training Center, January to April 2017 using a randomized block design with 4 (four) treatments, repeated three times. ie Without Bokashi (B0), Bokashi 5 ton / ha (B1), Bokashi 7.5 ton / ha (B2), and Bokashi 10 ton / ha (B3). This study aims to determine the effect of bokasi in increasing soybean production of anjasmoro varieties. The data was processed by fingerprint and if there is difference of median value of treatment followed by the test of the Smallest Different Beda (BNT), at 5% level. The results showed that the application of bocation had no significant effect on the number of branches per plant, the number of books per plant and the number of root nodules per plant. The application of 15 ton / ha of bokasi gave seed yield per plant and per heavier plot compared with other treatments ie 13.17 g per plant and 16.64 kg per plot. Bokashi 5 ton / ha (B1), and Bocation Applications of 10 ton / ha (B2), were not significantly different, ie 11.33 g and 14.16 kg per plot respectively (equivalent to 1 , 42 ton / ha); 10.67 g and 13.52 kg per plot (equivalent to 1.35 ton / ha) 11.67 g and 14.90 kg per plot (equivalent to 1.49 ton / ha)